CAPITAL MARKET AND ENGLISH COMPETENCY IN ACCOUNTING STUDENT’S PERSPECTIVE DURING PANDEMIC COVID-19 - Putri Puspita Ayu., S.Pd., M.Ak; Tika Septiani (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
AbstractToday, Indonesians are increasingly aware of the importance of investing, Technical and Fundamental Analysis is an analytical tool to assess the company's performance. By using this analysis, it is expected that investors and potential investors can assess the feasibility of the company before making capital market investments. As a student of the School of Economics, the assessment of investment is not unfamiliar. Therefore, the purpose of this study is to test the understanding of capital market accounting and the English understanding of basic technical analysis. The population of this research is students from the UGJ School of Economics. He has signed up for English and business English courses, and has a family of financial accounting and capital markets, and has obtained 154 students as research interviewees. Research data is analyzed using descriptive statistics and multiple regression analysis.While the feasibility of regression models is assessed using the Classical Assumption Test, Hypothesis Test, and Determination Coefficient Test. The results of this study show that Understanding capital market accounting and understanding of English have an effect on understanding technical and fundamental analysis.Keywords: Technical Analysis, Fundamental Analysis, Capital Market, English Competency